Selectively T cell phosphorylation activation of azvudine in the thymus tissue with immune protection effect - Ning Sheng; Rui Li; Yang Li; Zhe Wang; Lulu Wang; Yuhuan Li; Jinlan Zhang; Jiandong Jiang (Elsevier, 2024)
Thymus is the important immune organ, responsible for T cell development and differentiation. The lower circulating T counts have been observed in patients who died from COVID-19 compared with survivors. Azvudine, also known as FNC, is a thymus-homing anti-SARS-CoV-2 drug in treating COVID-19 patients. In this study, single-cell transcriptome, proteomics, and parallel reaction monitoring (PRM) were applied to insight into the activation process of FNC in rat and SARS-CoV-2 rhesus monkey thymus. The results indicated that thymic immune cells possess a robust metabolic capacity for cytidine-analogue drugs such as FNC. Key enzymes involved in the FNC phosphorylation process, such as Dck, Cmpk1, and Nme2, were highly expressed in CD4+ T cells, CD8+ T cells, and DP (CD4+ CD8+) cells. Additionally, FNC could upregulate multiple phosphorylated kinases in various cell types while downregulating the phosphatases, phosphoribosyl transferases, and deaminases, respectively. The robust phosphorylation capacity of the thymus for cytidine analogue drug FNC, and the activation effect of FNC on the NAs metabolism system potentially contribute to its enrichment in the thymus and immune protection effect. This suggests that it is crucial to consider the expression level of phosphorylation kinases when evaluating NA drug properties, as an important factor during antiviral drug design.